2012
DOI: 10.1117/1.jbo.17.1.017007
|View full text |Cite
|
Sign up to set email alerts
|

Identifying compositional and structural changes in spongy and subchondral bone from the hip joints of patients with osteoarthritis using Raman spectroscopy

Abstract: Raman microspectroscopy was used to examine the biochemical composition and molecular structure of extracellular matrix in spongy and subchondral bone collected from patients with clinical and radiological evidence of idiopathic osteoarthritis of the hip and from patients who underwent a femoral neck fracture, as a result of trauma, without previous clinical and radiological evidence of osteoarthritis. The objectives of the study were to determine the levels of mineralization, carbonate accumulation and collag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(48 citation statements)
references
References 51 publications
(56 reference statements)
1
47
0
Order By: Relevance
“…[29,30] Thus, the two measures of bone composition that have been associated with osteoarthritis, osteoporosis and osteogenesis imperfecta, the phosphate-to-carbonate ratio and the mineral-to-collagen ratio, were the central focus of the study. [7][8][9][10] The phosphateto-carbonate ratio was accurately reconstructed by all three analyses, each having errors of 2% or less. The phosphate-tocarbonate ratio is easier to resolve than the mineral-to-collagen ratio since the phosphate and carbonate bands are unique to the target layer (bone) and so are less affected by being covered with a layer of skin/soft tissue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[29,30] Thus, the two measures of bone composition that have been associated with osteoarthritis, osteoporosis and osteogenesis imperfecta, the phosphate-to-carbonate ratio and the mineral-to-collagen ratio, were the central focus of the study. [7][8][9][10] The phosphateto-carbonate ratio was accurately reconstructed by all three analyses, each having errors of 2% or less. The phosphate-tocarbonate ratio is easier to resolve than the mineral-to-collagen ratio since the phosphate and carbonate bands are unique to the target layer (bone) and so are less affected by being covered with a layer of skin/soft tissue.…”
Section: Discussionmentioning
confidence: 99%
“…For example, it has been shown that excised subchondral bone from osteoarthritic hip joints can have decreased mineral-to-collagen ratio (~15%) and decreased phosphate-to-carbonate ratio (~20%). [7] It has also been shown that excised subchondral bone from osteoarthritic knee joints can have increased mineral-to-collagen ratio (~3%) and decreased phosphate-to-carbonate ratio (~6%). [8] Studies of excised bone from patients who had suffered osteoporotic fracture of the femur suggest that the bone in their femoral neck has an increased mineral-to-collagen ratio (~30%) [9] and studies of excised bone from mutant mice models of osteogenesis imperfecta suggest the mineral-to-collagen ratio is increased (~20%).…”
Section: Introductionmentioning
confidence: 99%
“…36 Given low instrument polarization and results from less polarization sensitive carbonate and Amide III bands, analysis of bone from osteoarthritic patients on different load bearing surfaces can be interpreted as a largely compositional effect. 53 Phase mismatch of ν1 Phosphate/CH 2 [see Figs. 2 and 6(e)] may have contributed to biomechanical correlation due to use of a commercial confocal system, 24 thereby indicating a Table 3 Paired phase difference between selected Raman peak ratios and overall variance of peak ratios were estimated for bone and tooth rotation using the unaltered polarization instrument.…”
Section: Discussionmentioning
confidence: 99%
“…In some of these situations, ratios of Raman bands can be useful indicators. Buchwal et al used Raman band ratios as indicators of bone structure and composition [467] while Li et al used band ratios to measure the effects of maleic acid on human sperm [468].…”
Section: Direct Peak Analysismentioning
confidence: 99%